Morbidity pattern among the adolescents attending the rural health training centre in Nagaon, Barpeta District, Assam - Boruah, Beeva; Hajong, Sudipta; Hakmaosa, Annamika (International Journal Of Community Medicine And Public Health, 2020)
Background: WHO (World Health Organization) defines adolescence as the segment of life between the ages of 10 and 19 years. The health problems of adolescents are very different from those of younger children and adults. Adolescent’s problems constitute a bulk of morbidities, which are unrecognized and uncared iceberg of disease burden. Moreover, the complex psychosocial morbidities and high risk behaviour of adolescents have been recognized as a threat to survival, growth and development. The objective of this study was to study the morbidity pattern prevalent among adolescents who attended the rural health training centre in Nagaon, Barpeta district, Assam. Methods: A cross sectional study was carried among 140 adolescents aged between 10 to 19 years, who visited the rural health training centre during the study period using convenient sampling technique. Data collection was done by using a semi structured questionnaire. A detailed history was taken regarding present and past illness. General and systemic examination was done. Anthropometric measurements were taken. Data analysis was done using SPSS version 17 and the results expressed in percentages. Results: The most common morbidity was anaemia, seen in 69.29% adolescents (males-66.04% and females-71.26%), followed by upper respiratory tract infection 37.14% (males-44.51% and females-34.48%) and dental problems 28.57% (males-28.30% and females-28.74%). Conclusions: Anaemia is the most common morbidity seen among adolescents in the present study. Early detection of the morbidities through regular survey will help in the prompt treatment and prevention of serious complications.